TEACHER-STUDENTS CLASSROOM INTERACTION IN TEACHING AND LEARNING ENGLISH - Ni Made Rianita (IKIP Siliwangi, 2024)
This study attempts to expound on the interactions that take place in the classroom between seventh-grade students and English teacher. This study was taken place in SMP Negeri Satu Atap 1 Sawan. A descriptive qualitative study on teacher and student interactions was used in this reasearch. Several data collection procedures were followed in order to analyze the data. To collect the data, the researchers conducted interviews, field notes, and observation. The classroom interactions were observed by the researcher to know the interactions between the teacher and the students (as the participants) in teaching and learning English. The findings demonstrated how the instructor actively engaged the students in the process of learning. Because the students cooperated in joining the lesson and the teacher used a teaching strategy to make the content easier to learn, the activities in the classroom went off without a hitch. The majority of the interactions, it was discovered, were arranged by the teacher. Finding the right teaching strategy and approach is crucial if you want your students to become more confident in their ability to strike up conversations. In addition, the instructor needs to practice effective time management while using a certain teaching strategy.